Reproductive biology of 58 fish species around La Réunion Island (Western Indian Ocean): first sexual maturity and spawning period - Kélig Mahé; Julien Taconet; Blandine Brisset; Claire Gentil; Yoann Aumond; Hugues Evano; Louis Wambergue; Romain Elleboode; Tévamie Rungassamie; David Roos (Journal of Animal Reproduction and Biotechnology, 2024)
Background: The biological information of fish, which include reproduction, is the prerequisite and the basis for the assessment of fisheries. Methods: The aim of this work was to know the reproductive biology with the first sexual maturity (TL50) and the spawning period for 58 mainly fish species in the waters around La Réunion Island (Western Indian Ocean). Twenty families belonging to the Actinopterygii were represented (acanthuridae, berycidae, bramidae, carangidae, cirrhitidae, gempylidae, holocentridae, kyphosidae, labridae, lethrinidae, lutjanidae, malacanthidae, monacanthidae, mullidae, polymixiidae, pomacentridae, scaridae, scorpaenidae, serranidae, sparidae; 56 species; n = 9,751) and two families belonging to the Elasmobranchii (squalidae, centrophoridae; 2 species; n = 781) were sampled. Between 2014 and 2022, 10,532 individuals were sampled covering the maximum months number to follow the reproduction periods of these species. Results: TL50 for the males and the females, respectively, ranged from 103.9 cm (Acanthurus triostegus) to 1,119.3 cm (Thyrsitoides marleyi) and from 111.7 cm (A. triostegus) to 613.1 cm (Centrophorus moluccensis). The reproduction period could be very different between the species from the very tight peak to a large peak covered all months. Conclusions: Most species breed between October and March but it was not the trend for all species around La Réunion Island.